Pengaruh Manfaat Dan Kemudahan Terhadap Minat Menggunakan BSI Mobile Pada Masyarakat Di Desa Sungai Tering Kecamatan Nipah Panjang - Supriadi Supriadi; Erwin Saputra Siregar; Aztyara Ismadharliani (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The development of information technology is currently changing the minds of customers or consumers in carrying out various transaction activities in the banking world, where customers prioritize aspects of convenience, flexibility, efficiency and simplicity. Mobile banking technology is a type of service provided by banks to their customers so that they can carry out their banking activities at any time without having to come to the bank. The purpose of this study was to determine the effect of benefits and convenience on the interest in using BSI Mobile in the community in Sungai Tering Village, Nipah Panjang District. This type of research uses quantitative methods. The population in this study consisted of 100 respondents. This research uses a random sampling technique, namely taking the population based on the area of the object of this research. The data analysis technique used to answer all the problem formulations uses multiple linear regression analysis using the SPSS version 23 program. The results of the t test show that the benefits variable has a tcount value of 1.870 > ttable 1.660 Then H1 is accepted, the convenience variable has a tcount value of 5.676 > ttable 1.660 then H2 is accepted, and the R2 test is 0.678, this means that the interest variable can be explained by the perception variable convenience, benefits and safety. The t test results of the variable that is very influential in using mobile banking, namely the convenience variable, has a t value of 5.676.